Impact Of Culture Change On Commerce In Northern Corridor Economic Region Urban - YUSOFF, NORANIZA (Human Sustainability Procedia, 2018)
Urban produce affluence and expenditure chances for dwellers, nevertheless, the assumption of located way of life encourages and produces possibility for greater various impacts that possibly also have vital strategy consequences. Largely interest is the deficient of robust investigation performed on the cultural, economic, political, limited period and long-run impacts of cultural designing. This research is a basic research aims to explain the relationship between culture change and commerce through quantitative approach. Data collection by cross-sectional survey using a questionnaire took place in the year 2016 involved 434 respondents that the population of several cities in study areas namely Ipoh, Perak; Georgetown, Penang; and Sungai Petani, Kedah.Objective of this study is to determine the relationship between culture change and commerce in urban area of Northern Corridor Economic Region. Research question of this study is why culture change influence commerce in urban area? Data analysis consists of Spearman correlation, Ordinal Regression and scatterplot. Findings signify there is no association between the variables through scatterplot diagram. However, coefficient value of Spearmen correlation implies positive strong correlation that there is relationship between culture change and commerce